A new black fly species of the Simulium (Gomphostilbia) epistum species-group (Diptera: Simuliidae) from Thailand - Hiroyuki Takaoka (2018)
© 2017 Elsevier B.V. A new species of black fly, Simulium (Gomphostilbia) isanense, is described based on females, males, pupae and mature larvae from Thailand. This new species is placed in the Simulium epistum species-group of the subgenus Gomphostilbia Enderlein. It is characterized by the pupal gill with eight filaments arranged as 3 + 3 + 2 from dorsal to ventral, of which an inner filament of the ventral pair is slightly longer than its counter filament. Taxonomic notes are provided to distinguish this new species from S. (G.) angulistylum Takaoka & Davies from Peninsular Malaysia, and three other related species. The difference between this new species and S. (G.) angulistylum is supported by genetic distances using the mitochondrial COI gene.